Payments and Patient Cost Sharing for Prostate Biopsies According to Image Guidance, Practice Site and Use of Anesthesia. Issue 2 (3rd March 2020) - Leung, Andrew K.; Patil, Dattatraya; Howard, David H.; Filson, Christopher P.
Abstract: Introduction: Use of magnetic resonance imaging for prostate biopsies has increased and more biopsies are performed in nonoffice based settings. These changes will likely impact payments related to prostate biopsies. Methods: Using private insurance claims from 2009 to 2015 we identified men who underwent transrectal ultrasound guided (CPT 55700) or transperineal (CPT 55706) prostate biopsies. We assumed any magnetic resonance imaging of the pelvis within 3 months prior to biopsy was for image based guidance. We assigned biopsy site as being performed in the office, ambulatory surgical center or hospital. Use of anesthesia was based on CPT codes 00100–01999. Our primary outcome was aggregate payments for anesthesia, pathology, imaging and procedural services. We also studied patient out-of-pocket costs. Multivariable regression was used to generate predicted payments based on magnetic resonance imaging performance, anesthesia and site of biopsy. Results: We identified 304, 388 biopsy episodes, of which 2.2% were magnetic resonance imaging guided and 0.7% were transperineal. Median cost of magnetic resonance imaging guided biopsies was greatest at 4, 396 (IQR 2, 784–7, 127) compared to the costs of transperineal and transrectal ultrasound guided biopsies. Imaging accounted for the greatest share of magnetic resonance imaging guided biopsy costs (median 1, 704, IQR 975–3, 043). Magnetic resonance imaging guided biopsies in a hospital with anesthesia had the highest cost at 5, 832 per episode (95% CI 5, 732–5, 934). There was a fivefold difference in patient cost sharing between the least expensive (transperineal, office and no anesthesia 168) and most expensive (magnetic resonance imaging guided, ambulatory surgical center with anesthesia 891) modality. Conclusions: Total and out-of-pocket costs for prostate biopsies vary substantially based on modality, location and anesthesia use.